Incidence of Pediatric Pulmonary Tuberculosis in East Java, Indonesia - Nabila Putri Himawati Ramadhani; Ni Made Mertaniasih; Retno Asih Setyoningrum; Arief Bakhtiar (Indonesian Journal of Tropical and Infectious Disease, 2026)
Tuberculosis (TB) remains one of the world’s leading infectious diseases and a cause of morbidity and mortality, especially among children. Despite being both preventable and curable, TB affected an estimated 10.6 million people globally in 2023, including 1.3 million children. In Indonesia, the world’s second-highest TB burden country, pediatric TB is often underdiagnosed due to nonspecific symptoms and difficulty in bacteriologic confirmation. This study describes the incidence and trend of pulmonary TB among children aged 0–14 years in East Java, specifically focusing on data from Surabaya, from 2019 to 2024, and evaluates the role of GeneXpert MTB/RIF and GeneXpert Ultra in improving pediatric TB detection. This descriptive cross-sectional study used secondary data from the East Java Provincial Health Office and the National TB Program (SITB). Annual pediatric TB cases and population data were used to calculate incidence (per 100,000 children). GeneXpert test totals were used to compute the Pediatric TCM Intensity Index (cases per 1,000 tests). This study shows that pediatric TB incidence decreased from 59.0 per 100,000 in 2019 to 31.5 in 2020, then rebounded to 133.1 in 2023 and 124.7 in 2024. Molecular diagnostic capacity increased to 274 connected GeneXpert units and > 375,000 tests by 2023, raising bacteriologic confirmation rates among children. Recently, the incidence of pediatric pulmonary TB in East Java has not yet decreased. Strengthening digital reporting systems, pediatric TB training, and field-based surveillance teams is essential for equitable diagnostic access and achieving Indonesia’s End TB 2030 targets.